1997
DOI: 10.3109/10428199709109170
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-Stimulating factor (G-CSF, filgrastim) after or during an intensive remission induction therapy for adult acute lymphoblastic leukaemia: Effects, role of patient pretreatment characteristics, and costs

Abstract: An early intensive anthracycline therapy can improve therapeutic outcome in adult acute lymphoblastic leukaemia (ALL) but is usually associated with marked myelosuppressive effects and significant morbidity by infections. To reduce this risk, we employed granulocyte colony-stimulating factor (G-CSF, filgrastim 5 microg/kg/d) as an adjunct to a myelotoxic, 14-day long induction regimen with idarubicin-vincristine-L-asparaginase-prednisone (IVAP). Owing to changes in study design, patients received 'late' (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…In fact, the use of ara‐C in a myeloablative regimen needs to be accompanied by an administration of colony‐stimulating factors, which are expensive. Indeed, to minimize the risk of infection in the induction period, which is the unavoidable complication of aggressive, marrow‐ablative chemotherapy, supportive care including prophylactic parenteral antibiotics and colony‐stimulating factors were administered 27,28 . In particular, growth‐factor support allowed the use of this dose‐intensive regimen at scheduled intervals with acceptable toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the use of ara‐C in a myeloablative regimen needs to be accompanied by an administration of colony‐stimulating factors, which are expensive. Indeed, to minimize the risk of infection in the induction period, which is the unavoidable complication of aggressive, marrow‐ablative chemotherapy, supportive care including prophylactic parenteral antibiotics and colony‐stimulating factors were administered 27,28 . In particular, growth‐factor support allowed the use of this dose‐intensive regimen at scheduled intervals with acceptable toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Three randomised studies demonstrated some advantages for G-CSF-treated patients in terms of CR rate, time to recovery of >1 × 10 9 l −1 neutrophils, incidence of febrile neutropenia and infectious complications, and reduced chemotherapy delays. Since the safety of this regimen and the lack of untoward effects were confirmed, the use of G-CSF at 5 mg/kg as an adjunct to induction therapy is recommended on a type 1 level of evidence [297][298][299], particularly with the more myelotoxic schedules employing anthracyclines on three consecutive days and in the elderly [300]. Delay of G-CSF administration until day 10 did not increase risk of neutropenic complications using the hyper-CVAD regimen [301].…”
Section: Growth Factors During Remission Inductionmentioning
confidence: 99%
“…Studies of cost-effectiveness, using yeast-derived GM-CSF or G-CSF have also shown the benefit of growth factors. [59][60][61][62][63] An exception has been a cost-effectiveness study using the more toxic E. coli-derived GM-CSF in AML. 64 Thus, cytokines should be routinely used, following induction therapy for acute leukemia, at least in those patients with anticipated high risk for therapy-related morbidity.…”
Section: What Is the Role Of Cytokines In Aml?mentioning
confidence: 99%